Afrikaans, American and British Models for South African English Lexicography: Racial Label Usage - Murphy, M. Lynne (Lexikos, 1997)
This article examines the treatment of racial labels in monolingual English dictionaries of South Africa. Considering past controversies regarding racist language in Afrikaans dictionaries and considering the changing role of English in democratic South Africa, we can expect that English dictionaries will be more carefully scrutinized in future for potential offence. With the boom in the South African lexicography industry, now is a prime time to reflect on the issues involved and suggest courses of action. This article places South African English dictionary traditions in a national and international context, by comparing the traditions and the roles of the languages in Afrikaans, British and American lexicographical traditions. While South African English lexicography is rooted in the British tradition, its possible evolution on the American model is demonstrated, and thus the role of the dictionary in a postcolonial community is briefly discussed.